In vivo imaging of patients with chronic pruritus of unknown origin reveals partial sweat duct obstruction with partial itch resolution upon retinoid treatment - Lim, Shi Yu Derek; Tan, Yingrou; Zhang, Yuning; Zhao, Xiahong; Ng, Lai Guan; Tey, Hong Liang (Frontiers in Medicine, 2023)
Background: Chronic pruritus of unknown origin (CPUO) is poorly understood and lacks effective treatment options.We aimed to elucidate abnormalities in the sweat apparatus of patients with CPUO, and to assess efficacy and safety of treatment with systemic retinoids.Methods: An initial case-control study included 20 affected patients and five healthy controls, for whom heat and sweating were induced, either through a standardized exercise protocol or ingestion of hot water. In vivo high-definition optical coherence tomography, whole-body starch-iodine testing, and skin biopsy for immunofluorescence staining were done to evaluate for sweat duct obstruction. A subsequent retrospective cohort analysis included 56 patients with CPUO, seen at an Itch subspecialty clinic of a single tertiary referral centre, who failed conventional treatments and were treated with isotretinoin and/or acitretin from May 2014 to November 2020. Treatment response to retinoids was defined as a sustained reduction in itch score of ≥2/10. Safety was assessed by proportion stopping treatment due to side effects.In vivo imaging in 19 (95%) patients revealed features of partial keratinaceous sweat duct obstruction with statistically significant luminal dilatation compared to controls.Immunofluorescence studies of three patients' paired lesional/non-lesional biopsies revealed dermcidin accumulation within sweat glands coupled with dermcidin leakage in itchy skin.Fifty-six patients (mean [SD] age 55.2 [17.5] years, 69.6% male) were treated with systemic retinoids. Mean (SD) duration of itch was 116.3 (140.4) months and mean (SD) itch score was 8.2 (1.8). Forty-one (73.2%) initially received isotretinoin, and 15 (26.8%) acitretin. At three months, mean itch score reduced by 2.38 (95% CI -3.2 to -1.6, p <.0001). Thirty-eight (67.9%) had a sustained response. Eight (14.81%) achieved an itch score of 0 or 1, with four stopping treatment for a mean (SD) of 318.5 (291.2) days without relapse. Eight (14.3%) stopped or switched retinoid due to adverse effects, with similar incidences between both retinoids, the commonest being dryness.Based on novel findings from physiological imaging studies identifying partial keratinaceous sweat duct obstruction in CPUO, we instituted systemic retinoid treatment to address the underlying pathology. In patients who failed conventional therapies, the treatment appears effective and safe.